Analysis of Employee Self-Development Need in the Era of Digitization - Gimin Gimin; Sri Kartikowati (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
This research aimed to analyze employees’ self-development needs during information digitization, specifically in the Faculty of Teacher Training and Education (FKIP) Riau University. Data were collected using Google Form questionnaire, obtaining a 79.03% response rate. The data collected were analyzed using descriptive statistics and regression analyses. The result showed that (1) Most employees had a strong understanding of primary duties and functions, suggesting a "high" proficiency level; (2) Technical knowledge and skills had low scores for the majority, while work attitude mostly fell in the "medium" range; (3) Work motivation was largely classified as "medium", with employees showing interest in self-development opportunities, such as job training through mentoring and peer groups. Regression analysis showed that work ability and role clarity had a joint significant influence on employees’ work motivation. However, each factor did not show a significant effect individually. This result showed the importance of ensuring all employees have both adequate work ability and role clarity. Based on this result, it was recommended that the management of FKIP Riau University devise employees’ development model. This model should prioritize enhancing work ability and clarifying roles to foster motivation and organizational effectiveness.